Resepsi Dialog Antar Agama di Media Sosial: Studi Kasus Youtube Deddy Corbuzier Dalam Tagar LoginCloseTheDoor - Trendi, Hadiana; Aulya Afifah, Tsaqifa; Azami, Hadiana Trendi; Afifah, Tsaqifa Auliya; Mumtaz, Ghina Syaikhah (Jurnal Lektur Keagamaan, 2024)
The trend of using social media for da'wah in Indonesia has sparked diverse perspectives. While some religious studies emphasize the negative aspects of social media, such as exclusivism and extremism, interreligious dialogue studies often focus on theological and ritualistic aspects. This study addresses a gap by analyzing the reception of interreligious dialogue on social media, specifically through a case study of Deddy Corbuzier's YouTube channel using the hashtag #LoginCloseTheDoor. Utilizing a qualitative approach, this research examines audience responses, both positive and negative, and the potential social impact of these dialogues. The study seeks to answer two key questions: How does Deddy Corbuzier's interreligious dialogue content under the hashtag #LoginCloseTheDoor influence social media users? What factors drive netizens to engage enthusiastically with this content? Findings indicate that the "LogInCloseTheDoor" content effectively introduces religious concepts and receives positive public reception, reflecting successful religious adaptation and high engagement.